A Cybersecurity Experience with Cloud Virtual-Remote Laboratories - Llanos Tobarra; Antonio Robles-Gómez; Rafael Pastor; Roberto Hernández; Andrés Duque; Jesús Cano (Proceedings, 2019)
In recent years, there has been a great increase in the daily use of technology, to the extent that people are almost permanently connected to the Internet. In our particular case, we are interested in maintaining information security, which is known as cybersecurity. Traditional security techniques are obsolete, so it becomes necessary to acquire new practical skills with a problem-based learning methodology. Therefore, this paper presents a new approach based on virtual-remote laboratories for the creation of dynamic cybersecurity scenarios in the Cloud. Additionally, the factors that influence the intentions of the participants in the subject employed for this work have been studied. This information has been gathered by using both the answers obtained from an opinion survey and available information in the activity records of the educative labs.